Energy Systems and Environment 2018
DOI: 10.5772/intechopen.73833
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Derived from Agricultural Waste Biomass Act as a Clean and Alternative Energy Source of Fossil Fuel Inputs

Abstract: In this study, pyrolysis was used to upgrade the agricultural biomass waste (ABW) and increase its energy at pyrolysis temperatures ranging from 350 to 950 C and a residence time of 60 minutes. The produced biochars were characterized and their fuel qualities (such as, fixed carbon & carbon percentage, gross calorific value, pH and surface area) were evaluated. Physiochemical analysis showed that the biochar has improved fuel qualities compared to the raw biomass, such as decreased volatile matter, increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
0
14
0
1
Order By: Relevance
“…(2016), who found that PAS‐FTIR is capable of providing valuable information regarding P speciation in biochars produced by the solid fraction of digestate and bone meal at very high temperatures (up to 1,050 °C). In addition, Liu, He, and Uchimiya (2015), Reeves (2012), and Suman and Gautam (2018) have also recorded almost featureless DR‐FTIR, ATR‐FTIR, and transmission spectra, respectively, for biochars produced from agricultural by‐products through pyrolysis at temperatures above 600 °C.…”
Section: Resultsmentioning
confidence: 99%
“…(2016), who found that PAS‐FTIR is capable of providing valuable information regarding P speciation in biochars produced by the solid fraction of digestate and bone meal at very high temperatures (up to 1,050 °C). In addition, Liu, He, and Uchimiya (2015), Reeves (2012), and Suman and Gautam (2018) have also recorded almost featureless DR‐FTIR, ATR‐FTIR, and transmission spectra, respectively, for biochars produced from agricultural by‐products through pyrolysis at temperatures above 600 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Range obtained for VM content i.e., 60-85% in studied biomass is as high as any of the fossil fuels [49,50], which can initiate ignition even at lower temperature (150-250°C) and support combustion processes, whereas in other fossil fuels like coal for initiating any combustion process the required ignition temperature ranges 260-450°C. Biomass also have less in nitrogen and sulphur content than any other fossil fuels (coal), which indicates less evaluation of NOx and SOx during combustion processes [48]. These above characteristics of biomass are importance with respect to the design and operation of combustion systems for agricultural biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural biomass also has higher volatile matter [47] than coals. Agricultural biomass usually consists of 70-80% VM whereas coal consists of 10-50% VM [48].…”
Section: Combustion Study For Biomass Materialsmentioning
confidence: 99%
“…Most agricultural solid waste can be converted into biochar [14,15] and there are different methods for the production of biochar from this waste stream. These include hydrothermal carbonisation [16], gasification and pyrolysis [15].…”
Section: Conversion Of Agricultural Waste Into Biocharmentioning
confidence: 99%
“…These include hydrothermal carbonisation [16], gasification and pyrolysis [15]. However, pyrolysis is the most used method for the production of biochar [14]. This involves the irreversible thermal decomposition of organic substances at higher temperatures under anoxic conditions.…”
Section: Conversion Of Agricultural Waste Into Biocharmentioning
confidence: 99%